ZAKAZ OBCIĄŻANIA NIERUCHOMOŚCI POSAGOWYCH W RZYMSKIM PRAWIE KLASYCZNYM - Stępkowska, Agnieszka (Zeszyty Prawnicze, 2017)
Prohibition of Creation of Real Security over a Dowry in Classical Roman Law Summary Lex Iulia de fundo dotali, as enacted in 18 BC, prohibited alienation of immovable property constituting a dowry. Three passages from the Justinian’s Com pilation inform that the lex Iulia also prohibited creation of a real security over the dowry immovables. The first passage, by Gaius (D. 23,5,4) says the lex Iulia prohibited the immovables to be either pledged or alienated (Lex Iulia, quae de dotali praedio prospexit ne id marito liceat obligare aut alienare). The other two passages come directly from Justinian and state that lex Iulia prohibited mortgaging (hypothecare) of dowry immovables even in case the wife accepted creation of such a security, whereas the wife’s consent enabled a lawful alienation thereof (C. 5,13,1,15; I. 2,8 pr.). The paper concentrates on two issues. The first is the very existence of the said prohibition in the classical Rom an law. The second one focuses on wife’s consent to the real security over her dowry, which - as Justinian claimed - had no legal effect. As concerns the first issue, analysis contained in the paper leads to a conclusion that the lex Iulia de fundo dotali did not expressly provide for the establishment of a real security over dowry. Nevertheless, evolution of the Roman jurisprudence in respect to pignus resulted in the 2nd century AD with the com m on agreement among jurists that the establishment of pignus enclosed also a tacit consent for alienation o f the thing given in pignus in case the debt was not paid. In this context a prohibition of alienation as contained in lex Iulia had to be understood as concerning also creation of the real security (pignus or hypotheca) over dowry immovables. Otherwise, lex Iulia could be circumvented by means o f establishment of a real security leading in fact to alienation. The above conclusion also allows to solve the second problem. Justinian’s statements that lex Iulia prohibited creation of a real security over dowry despite the wife’s consent are true exposition of the classical law in so far as Justinian thought about the consent to the establishment of the real security. It seems uncontroversial, the husband was able to create valid real security over dowry, if the wife consented to the alienation of a fundus dotalis. The wife’s consent to pledge the land being her dowry was not enough as the woman might not be conscious, that she consents to possible alienation. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />